AirGuardian: Real-Time IoT-Based Air Pollutant Monitor System - ARIFF, MUHAMMAD DANISH; Marjudi, Suziyanti (Applied Information Technology And Computer Science, 2025)
The use of the internet of things has been widely applied in the daily routine of life and surrounding conditions. AirGuardian: Real-Time IoT- Based Air Pollutant Monitor System was developed based on IoT technology to help its users monitor the quality of surrounding air as there was no system to monitor the air pollution developed for schools. The main objective of this system development is to develop a real-time IoT-Based Air Pollutant Monitor system using a structured approach and using web-based approach and IoT based approach and to test the developed system for user acceptance by using the Agile methodology. The system will show about the air pollution reading and can be used for early precaution for the students, school staff and residents around the school compound. By using this system, it can help students and school staff to gain awareness on air pollution and this system can be integrated with other system as well.